UZBEKISTAN IS ON THE WAY TO IMPORTANT REFORMS IN THE PREVENTION OF EMERGENCY SITUATIONS - A. Norboyev (Western European Studies, 2025)
This article is devoted to various types of emergencies, which are becoming one of the most global issues in the world today, and their solutions in our country. The article analyzes the role of the human factor in the occurrence of emergencies and the systems developed to prevent such situations in our Republic.
Keywords: emergency situations; technogenic situations; socio-political system